Efficient regeneration protocol for producing true-to-type oil palm (Elaeis guineensis (jacq.) through somatic embryogenesis from immature male inflorescence - B. Kalyana Babu; R.K. Mathur; K. Suresh; G. Ravichandran; B. Susanthi; G.B. Patil; Narayana Ruthweek; M. Mahesh (Heliyon)
Producing homogeneous planting material in oil palm poses a significant challenge, which can be addressed through somatic embryogenesis. This study successfully achieved somatic embryogenesis using immature male inflorescence from Tenera hybrid. Modified Eeuwens medium yielded better results than the Murashige and Skoog (MS) and CHU (N6) media when supplemented with 2,4-D, picloram and α-naphthaleneacetic acid (NAA). The Eeuwens (Y3) medium supplemented with picloram led to an increased callus percentage, ranging from 25 % to 63.7 %. The highest rate of somatic embryogenesis was observed with a combination of 2,4-D (16 mg/l), picloram (24 mg/l), and 2,4,5-trichlorophenoxyacetic acid (2,4,5 –T) (2 mg/l), resulting in an average embryogenesis percentage between 2.54 % and 7.24 %. The average embryogenesis percentage varied from. Additionally, the liquid media proved effective for root growth and proliferation (R2 medium), which included Indole-3-butyric acid (IBA) (2 mg/l) and NAA (0.5 mg/l), along with activated charcoal (100 mg/l). The elongated, nodular-shaped root-like structures developed into root primordial structures. This protocol will be instrumental in producing homogeneous oil palm planting material through micropropagation and cloning of mother palms, facilitating the establishment of semi-clonal seed gardens.